AB1483-PARE Development and adaptation of rheumabuddy for young people with jia, their families and people with ra residing in the uk. (12th June 2018) - Gilbert, A
Abstract : Background: The number of children and young people (CYP) with JIA needing support is on the increase as available allied services continue to face cuts and are under more pressure than ever. A valuable life skill for any CYP with a long-term condition is self-management, the ability to control emotions, learn resilience, communicate, work toward goals and ultimately improve their physical and emotional wellbeing. Methods: Rheumabuddy is a Danish app developed for children (aged over 12) adults in Denmark with RA. We were approached by the developers, Daman, in June 2016 and meetings and discussions followed regarding NRAS launching and distributing this innovative app in the UK. For a JIA audience, our main concerns were online child safety issues and whether the app could be used by younger children with JIA with their parents as well as by adults with RA. A survey of parents and young people with JIA and RA followed and after discussions with pilot users some adaptations were made, and child safety protection protocols were put in place between NRAS and Daman. Results: Daman appointed NRAS as its UK partner and NRAS undertook a soft launch of Rheumabuddy in November 2017. Conclusions: Since its launch, to date we have 2000 active users who are a mixture of children with JIA and their parents, adults with JIA and adults with RA. Here are some quotes from users: "Rheumabuddy has been so helpful and I am now able to track my progress which I can show my consultant. I would often forget how I felt 3 or 4 months ago" "The Rheumabuddy app was a way for my daughter to let me know how she felt each day, normally she doesn't like discussing it" We know that CYP are growing up in a challenging and fast changing world. The ability to use self-management strategies effectively is a skill that becomes very important for success as children grow into adulthood yet is hard to acquire through the NHS alone. Rheumabuddy encourages the self-monitoring and regular recording of key patient reported outcomes. Changes in symptoms over time can be displayed in graph format and can be shared with HCP's, family, and school. The collation of cumulative data around mood, pain and fatigue can, for example, lead to empowerment of the individual or family resulting in ability to effect positive lifestyle change in the person with JIA or RA. Acknowledgements: Anne Gilbert, Phil Baker, Ailsa Bosworth, Clare Jacklin, The National Rheumatoid Arthritis Society, Maidenhead and Daman Denmark Disclosure of Interest: None declared